Pathophysiology of hidradenitis suppurativa: a systematic review of the literature - Pedro Mendes-Bastos; Pedro Andrade; Joana Cabete; Inês Lobo; António F. Massa; Carmen Lisboa (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Hidradenitis suppurative (HS) is a multifactorial, recurrent, chronic inflammatory disease with a significant impact on patient's quality of life. The etiopathogenesis of this complex condition is not fully understood. In this systematic review, we aimed to address and clarify the role of genetics, immunity, endocrinology, and skin microbiome together with risk factors in HS etiopathogenesis. A systematic review, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, was performed using PubMed® and Web of ScienceTM databases on December 3rd, 2021, using patient/population, intervention, comparison and outcomes (PICO) criteria, limited to the last 10 years and English. Reports were analyzed by two independent reviewers. A total of 123 reports were included and divided into five sections: genetics, immunity, endocrinology, microbiome, and risk factors. Regarding genetics, up to 30-40% of patients have a positive family history of HS but only a small subset of these harbor genetic variants in components of the gamma-secretase complex. In fact, in more than 90% of HS patients, the genetic features contributing to disease development remain largely unknown. The immune response is also crucial for HS; it is characterized by antimicrobial peptide and proinflammatory cytokine dysregulation, namely interleukin (IL)-IL-23, IL-12, and Th17 immune response. This immune response in local and, consequently, systemic inflammation is amplified in patients with metabolic syndrome. The relationship between metabolic syndrome and HS is clear, and patients with metabolic syndrome have a higher risk of developing HS. The most recent evidence also associates skin microbiota dysbiosis with HS pathogenesis, contributing to local and systemic inflammation. Besides these intrinsic factors, the role of lifestyle in the development of HS is well accepted. Tobacco smoking and obesity are the main risk factors identified as contributing to HS pathogenesis. Chronic inflammation characterizes HS, a debilitating condition with a complex and multifactorial etiopathogenesis. The current model integrates genetics, immunity, endocrinology, and skin microbiome. Notwithstanding, efforts should be made to improve our comprehension of HS etiopathogenesis, hopefully leading to the development of more effective treatments.